2016
DOI: 10.1063/1.4939449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the C-bridge length on the ultraviolet-resistance of oxycarbosilane low-k films

Abstract: The effect of water uptake on the mechanical properties of low-k organosilicate glass J. Appl. Phys. 114, 084103 (2013) Depth dependence of ultraviolet curing of organosilicate low-k thin films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…It is necessary to note that the results of plasma treatment are highly sensitive to the pristine films structures. As it was pointed in 210,211 the films with backbone carbon (Si-R-Si) demonstrate the enhanced resistance to carbon loss upon exposure to either atomic oxygen or VUV radiation in the presence of O2 (VUV+O2). Also, Yasuhara et al 150 Besides, a shorter plasma exposure time can reduce the damage 102,147,192,212 .…”
Section: Iii2 Vuv/uv Radiation In Low-k Plasma Processingmentioning
confidence: 81%
“…It is necessary to note that the results of plasma treatment are highly sensitive to the pristine films structures. As it was pointed in 210,211 the films with backbone carbon (Si-R-Si) demonstrate the enhanced resistance to carbon loss upon exposure to either atomic oxygen or VUV radiation in the presence of O2 (VUV+O2). Also, Yasuhara et al 150 Besides, a shorter plasma exposure time can reduce the damage 102,147,192,212 .…”
Section: Iii2 Vuv/uv Radiation In Low-k Plasma Processingmentioning
confidence: 81%
“…The characteristic band of Sample 45E is located at ~720 cm −1 , which is correlated to the C–C bonds of ethylene bridges [ 26 , 27 , 28 ]. The distinctive peak of C–H bonds of methylene bridges in Sample 45M is located at ~1360 cm −1 [ 29 ], whose position differs markedly from the peak of C–H bonds of ethylene bridges in Sample 45E (~1415 cm −1 ) [ 30 ]. Some differences are also visible in the 3100–2800 cm −1 region.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we recently found that 1,4-phenylene rings can be more sensitive to thermal destruction in the presence of UV light even with λ > 200 nm [ 24 ]. It was shown that this effect is related to a shift of absorption edge in the UV region of 1,4-phenylene-bridged OSG to higher λ in comparison with ethylene/methylene-bridged [ 30 ] and methyl-terminated materials. It has also been shown that all these bridges are sensitive to the curing environment.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical structure of the films following the template removal at 400 °C was investigated by transmission FTIR measurements. Figure shows the characteristic absorptions of the ethylene‐bridged PMO in the ranges 500–1500 and 2700–4000 cm −1 providing evidence for the presence of intact Si−CH 2 −CH 2 −Si groups. The absorptions centred at 1273 and 1417 cm −1 are attributed to C−H deformation in the bridging ethylene groups.…”
Section: Figurementioning
confidence: 99%